Tetanus vaccine coverage in recommended and more than recommended doses among mothers in a West Cameroon health district: a cross sectional study [version 2; peer review: 1 approved, 3 approved with reservations, 2 not approved] - Trevor Anyambod Mboh; Linda Evans Eba Ze; Ruth Noutakdie Fossi; Dominique Majoric Omokolo; Jerome Ateudjieu; Etienne Guenou; Martin Nguetsop; Igor Nguemouo Nguegang (Gates Open Research)
Background: Vaccination is the best way to protect newborns and mothers against tetanus. The number of doses of Td vaccine recommended by the Expanded Program of Immunization is based on documented protective immune response. During this decade, the Foumban Health District (FHD) was the seat of an epidemic despite the satisfactory administrative immunization coverage. This study was conducted in 2019 in the FHD to assess tetanus vaccine coverage among mothers for their last pregnancy and the cumulative number of vaccine doses administered to the mothers. Method: This was a descriptive cross-sectional study conducted in the FHD in 2019. Mothers living in the district with at least one child younger than five years were included and were selected by random stratified cluster sampling. Trained surveyors used a face-to-face questionnaire, data extraction grid and data-tracking grid to review and collect data from antenatal care booklets, vaccination cards and the women’s own reports of immunization. The immunization coverage per vaccine dose and vaccination completeness rate were estimated. Results: From 621 women visited, 602 (96.9%) responded. A total of 176/511 women (34.4%) had evidence of vaccination. For the last pregnancy, the two-dose immunization proportion was 21.7% (111/511) for documented coverage and 47.6% (243/511) for undocumented coverage. 306/570 women (53.7%) had received more than the recommended five doses necessary for lifetime protection. The recruitment, two and five doses completeness rates were 99.9% (569/570), 95.8% (546/570) and 65.3% (372/570), respectively. Conclusion: More than half of mothers received more doses of tetanus toxoid vaccine than necessary in FHD. This increased the resources needed and the cost of vaccination. Health personnel should be trained and supervised to assess pregnant women’s vaccination status before planning the number of vaccine doses to be administered during pregnancy.